![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3x^2-2x+1 3x^4-8x^3-10x^2+8x-5 x^2-2x-16/3 3x^4-2x^3+x^2 -6x^3-12x^2+8x-5 -6x^3+4x^2-2x -16x^2+10x-5 -16x^2+32/3x-16/3 -2/3x+1/3
Vậy
- (3x4-8x3-10x2+8x-5):(3x2-2x+1) = \(x^2-2x-\frac{16}{3}\)dư \(\frac{-2}{3}x+\frac{1}{3}\)
x^2-1 x^4-2x^3+2x-1 x^2-2x+1 x^4-x^2 -2x^3+x^2+2x-1 -2x^3+2x x^2-1 x^2-1 0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=16-2x-x^2\)
\(A=-x^2-2.x.1-1+17\)
\(A=-\left(x^2+2.x.1+1\right)+17\)
\(A=-\left(x+1\right)^2+17\le17\)
Dấu = xảy ra khi :
\(x+1=0\Leftrightarrow x=-1\)
Vậy A max = 17 tại x = -1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^6-y^6\)
\(=\left(x^3\right)^2-\left(y^3\right)^2\)
\(=\left(x^3+y^3\right)\left(x^3-y^3\right)\)
\(x^6-y^6\)
\(=\left(x^3\right)^2-\left(y^3\right)^2\)
\(=\left(x^3+y^3\right)\left(x^3-y^3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm:
đk: \(\hept{\begin{cases}x\ge3\\x< -\frac{1}{2}\end{cases}}\)
Ta có: \(\sqrt{\frac{x-3}{2x+1}}=2\)
\(\Leftrightarrow\left|\frac{x-3}{2x+1}\right|=4\)
\(\Leftrightarrow\orbr{\begin{cases}\frac{x-3}{2x+1}=4\\\frac{x-3}{2x+1}=-4\end{cases}}\Leftrightarrow\orbr{\begin{cases}x-3=8x+4\\x-3=-8x-4\end{cases}}\Leftrightarrow\orbr{\begin{cases}7x=-7\\9x=-1\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=-\frac{1}{9}\end{cases}}\)
Mà \(3>-\frac{1}{9}>-\frac{1}{2}\) => \(x=-1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
TÌM X
a) (3x+2)(2x+9)-(6x+1)(x+2)=7
=> 6x2 + 31x +18 - 6x2 - 13x - 2 - 7 = 0
=> 18x + 9 = 0 => 9(2x + 1) = 0 => 2x + 1 = 0 => x = -1/2
b) (x-2)(x+5)-(x+3)(x+2)=-6
=> x2 + 3x - 10 - x2 - 5x -6 + 6 = 0 => -2x -10 = 0 => -2(x + 5) = 0
=> x + 5 = 0 => x = -5
c) 3(2x-1)(3x-1)-(2x-3)(9x-1)=0
=> 18x2 - 15x +3 - 18x2 + 29x -3 = 0 => 14x = 0 => x = 0
a) \(\left(3x+2\right)\left(2x+9\right)-\left(6x+1\right)\left(x+2\right)=7\\\Rightarrow 6x^2+31x+18-6x^2-16x-2-7=0\\ \Rightarrow18x+9=0\Rightarrow9\left(2x+1\right)=0\Rightarrow2x+1=0\Rightarrow x=-\frac{1}{2}\)
b) \(\left(x-2\right)\left(x+5\right)-\left(x+3\right)\left(x+2\right)=-6\\ \Rightarrow x^2+3x-10-x^2-5x-6+6=0\\ \Rightarrow-2x-10=0\\ \Rightarrow-2\left(x+5\right)=0\\ \Rightarrow x+5=0\\ \Rightarrow x=-5\)
c) \(3\left(2x-1\right)\left(3x-1\right)-\left(2x-3\right)\left(9x-1\right)=0\\ \Rightarrow18x^2-15x+3-18x^2+29x-3=0\\ \Rightarrow14x=0\\ \Rightarrow x=0\)
ta có 3*(3x-1/3)=5(x+1)-5
=>9x-1=5x
=> x=1/4